2020
DOI: 10.1001/jamapediatrics.2020.2209
|View full text |Cite
|
Sign up to set email alerts
|

Trends in Use of Advanced Imaging in Pediatric Emergency Departments, 2009-2018

Abstract: IMPORTANCEThere is increased awareness of radiation risks from computed tomography (CT) in pediatric patients. In emergency departments (EDs), evidence-based guidelines, improvements in imaging technology, and availability of nonradiating modalities have potentially reduced CT use. OBJECTIVE To evaluate changes over time and hospital variation in advanced imaging use.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
29
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 41 publications
(33 citation statements)
references
References 56 publications
4
29
0
Order By: Relevance
“…In the years prior to the pandemic, rates of advanced imaging increased at our institution, consistent with published trends across other pediatric emergency departments [ 25 ]. During the pandemic, imaging volumes for our pediatric ED decreased significantly, particularly when compared to predicted volumes based on increasing trends.…”
Section: Discussionsupporting
confidence: 81%
“…In the years prior to the pandemic, rates of advanced imaging increased at our institution, consistent with published trends across other pediatric emergency departments [ 25 ]. During the pandemic, imaging volumes for our pediatric ED decreased significantly, particularly when compared to predicted volumes based on increasing trends.…”
Section: Discussionsupporting
confidence: 81%
“…It is important to understand these findings in the context of national data. A recent study of 32 pediatric EDs found a 28% rate of MRI for ventricular shunt evaluation in 2018, 21 well below that during our intervention period, which supports our intervention’s impact.…”
Section: Discussionsupporting
confidence: 76%
“…Specifically, we evaluated patient age and sex, 22 insurance, 23 time and day of visit, 22 , 24 household income, 25 , 26 distance from the hospital, 27 complex chronic conditions, 26 3-day revisit, 28 , 29 hospitalization (including intensive care unit admission), 26 visit diagnosis, 13 and year. 6 We stratified patient age into clinically meaningful categories (<1, 1-4, 5-12, and 13-17 years) and defined the visit day as weekend vs weekday and arrival time as daytime (8:00 am to 3:59 pm ), evening (4:00 to 11:59 pm ), or overnight (12:00 to 7:59 am ). 30 Median neighborhood household income, presented as quartiles, was based on patient home 5-digit zip code in the PHIS and mapped to the American Community Survey 5-year data for 2014 to 2018.…”
Section: Methodsmentioning
confidence: 99%
“…However, for patients who are admitted from the ED, the data source does not distinguish between imaging performed in the ED and imaging performed as an inpatient on the same date. Therefore, and in keeping with prior work, 6,18 we defined imaging for admitted patients as follows: if ED arrival time was before 6 PM, we attributed imaging to the ED if it occurred on the day JAMA Network Open | Pediatrics of arrival; if ED arrival time was after 6 PM, we attributed imaging to the ED if it occurred on the day of arrival or the next day.…”
Section: Variables and Outcome Measuresmentioning
confidence: 99%
See 1 more Smart Citation